Addressing students with hearing impairment's current state and future needs: Reforming an inclusive science education - Adeniyi Michael Adeduyigbe; Anuoluwapo Elizabeth Adeduyigbe; Bamidele Emmanuel Tijani (International Journal of Studies in Inclusive Education)
This paper advocates for reforming science education to better accommodate students with hearing impairment, highlighting the unique challenges they face in traditional educational settings. Key obstacles include communication barriers, instructional methods primarily relying on auditory cues, and a lack of accessible educational materials. The paper emphasises the necessity of integrating visual learning tools and assistive technologies, which have been shown to enhance comprehension and engagement among learners with hearing impairment. Case studies illustrate successful implementations of inclusive practices, showcasing the positive impact on academic outcomes and social integration. However, significant limitations persist, including insufficient resources, inadequate teacher training, and budget constraints that hinder the effective use of technology. The paper concludes by urging educators, policymakers, and stakeholders to take immediate action toward creating more inclusive science classrooms, ensuring equitable access to quality education for all students.